Tied up in a sticky situation : identity disclosure and stigma management strategies of BDSM practitioners in Singapore - Tan, Bridget Wei Jing (2019)
This research explores the stigma faced by practitioners who are involved in sexually deviant practices of bondage, domination, submission/sadism, masochism (BDSM) in Singapore. Drawing on in-depth interviews conducted with members of the Singapore BDSM community, SG Learn and Play (SLAP!), we gathered and analysed data about BDSM practitioners’ personal encounters with stigma and their stigma management strategies. The data revealed that BDSM practitioners distanced themselves from stigmatisation by employing stigma management strategies such as concealment or selective disclosure, thus were rarely stigmatized by those whom they revealed their BDSM lifestyle to. In addition, the BDSM community is an important source for its practitioners to obtain emotional and practical support. Our findings suggest that due to the unique position of BDSM whereby it is technically legal yet not socially accepted in Singapore, the BDSM community employs a stigma management strategy which we termed as “pragmatic inconspicuity”.